ARGUMENTS FOR A KIERKEGAARDIAN REREADING OF POSTMODERNITY AT THE LEVEL OF A KEY-(ARCHI)TECTONIC SHIFT: THE KAIROS - Francisc-Norbert ORMENY (Studia Universitatis Babeș-Bolyai. Philosophia, 2015)
The present study attempts to legitimize a re-reading of postmodernity’s utter confusions and con-fusions (modern man’s loss of the sense of the Self, his weird panic attacks, his dissipations, his loss of personal and collective magnetisms [of faith], his parapsychological and crypto-phenomenological impels to disengage from his objective boundaries) at the level of that special type of vortical dynamics induced by Kierkegaard’s notion of leap (kairos). The accumulated pain coming towards us from the tension of the eternal human incompleteness (constant para-archi-tectonic inconsistency, impossibility to complete cycles, ontological instability and resistance to total representations) of paradoxes proves itself to be the very “fuel” necessary in the enactment of the leap (of the kairos) from one existential level to another. In essence, it is a chaos-filled transition towards the origin of chaos and of creation, towards the uncreated as generous-potency-to-be-apprehended and internalized by the stellar desirer and by the stellar seducer. Every kairos is a personal (and heavily personalized) spiritual exercise for re-enacting the primal movement of the uncreated towards the fragile intricacies of creation. It is an enthroned heterogeneity with its crown made of the fertile plasma of all boiling homogeneities.